Impacts of shared home range on human-wildlife conflicts - Upadhayay, Pooja; MacDonald, Suzanne E.; Schoof, Valérie A.M. (Frontiers in Conservation Science, 2025)
Human-wildlife conflicts (HWCs) are becoming increasingly common in landscapes altered by human activity, often threatening both livelihoods and wildlife conservation. We investigated HWCs in two communities: Bbaale village near Nabugabo Research Site in Uganda (73 households surveyed in 2019) and Manyangalo village near the Lewa-Borana Conservancy in Kenya (50 households surveyed in 2022) using descriptive statistics. We assessed how socioeconomic factors influenced household responses to HWCs using ordinal logistic regression models and explored community perceptions of living near a research site or conservancy. Our results showed that HWCs at Bbaale were reported as more severe (62%), often involving crop damage and livestock losses, while encounters near Manyangalo occurred more frequently (86%) but caused less damage. Households in Bbaale used a range of management strategies, including banging tins (86%), using dogs (60%) and scarecrows (59%), whereas Manyangalo residents primarily relied on noisemaking (100%). Larger cultivable areas were associated with more reported conflicts, and individuals with secondary education reported less severe impacts. Despite differences in HWC experiences, most respondents (Bbaale: 88%, Manyangalo: 86%) in both villages expressed positive views of the research site or conservancy, suggesting local support for conservation initiatives. These findings emphasize the importance of tailoring HWC management strategies to local conditions and community needs.